2013
DOI: 10.1088/0957-4484/24/35/355601
|View full text |Cite
|
Sign up to set email alerts
|

High yield formation of lipid bilayer shells around silicon nanowires in aqueous solution

Abstract: The combination of nanoscaled materials and biological self-assembly is a key step for the development of novel approaches for biotechnology and bionanoelectronic devices. Here we propose a route to merge these two subsystems and report on the formation of highly concentrated aqueous solutions of silanized silicon nanowires wrapped in a lipid bilayer shell. We developed protocols and investigated the dynamics of lipid films on both planar surfaces and silicon nanowires using fluorescence recovery after photobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…These curved regions can be uniquely valuable in systematic studies of the influence of curvature on biomolecules at lipid membranes. Further, while it has been shown that lipid bilayers form on silicon nanowire field effect transistors, , as well as on a single silicon nanowire laid horizontally and nanowires dispersed in solution, the possibility to use arrays of vertical nanowires–bilayer hybrid structures opens up the capabilities to study interactions at the membrane interface using a range of surface sensitive techniques. Unlike dispersed nanowires, the nanowires here are vertically aligned and attached to a surface, a feature that will potentially enable us to localize and track interactions taking place at any individual nanowire.…”
mentioning
confidence: 99%
“…These curved regions can be uniquely valuable in systematic studies of the influence of curvature on biomolecules at lipid membranes. Further, while it has been shown that lipid bilayers form on silicon nanowire field effect transistors, , as well as on a single silicon nanowire laid horizontally and nanowires dispersed in solution, the possibility to use arrays of vertical nanowires–bilayer hybrid structures opens up the capabilities to study interactions at the membrane interface using a range of surface sensitive techniques. Unlike dispersed nanowires, the nanowires here are vertically aligned and attached to a surface, a feature that will potentially enable us to localize and track interactions taking place at any individual nanowire.…”
mentioning
confidence: 99%
“…The fluorescence intensity inside the photobleached area was quantified using ImageJ in order to generate fluorescence recovery curves. The half-time of recovery ( t 1/2 ) was obtained from the fitting of the obtained curves (and then the diffusion coefficient ( D ) was estimated using the following equation: D = (0.88 × w 2 )/4 t 1/2 , where w indicates the radius of the bleached area). , …”
Section: Methodsmentioning
confidence: 99%
“…Since cell membranes play a critical role in cellular interactions, studies have recently been carried out to encapsulate NWs in a lipid bilayer as to mimic a cell membrane [9][10][11][12]. The electrical detection of ion transport through pore channels in a lipid bilayer coated Si NW was recently demonstrated in [13], revealing the potential of using Si NW devices as artificial cell constructs.…”
Section: Introductionmentioning
confidence: 99%
“…While the in-situ formation of lipid bilayers on Si NWs was studied using fluorescence microscopy in [12], real-time electrical measurements performed to analyze the temporal effect of the membrane formation process on NW conductivity were absent. A change in the electrical resistance for a bilayer coated vs. uncoated NW was demonstrated only ex-situ by Misra et al [13] and Martinez et al [10].…”
Section: Introductionmentioning
confidence: 99%